Distribusi Zakat sebagai Instrumen Pengentasan Kemiskinan dalam Praktik Lembaga Amil Zakat di Indonesia - Musnaeni Musnaeni; Annisa Ma’rifatul Khasanah (STIKes Ibnu Sina Ajibarang, 2025)
This research discusses zakat distribution as a strategic instrument in poverty alleviation through the practices of Amil Zakat Institutions in Indonesia. The background of this study stems from the persistently high poverty rate and the great potential of zakat as a source of religious social funds. The objective of this research is to analyze the effectiveness of zakat distribution by Amil Zakat Institutions in reducing poverty levels. The research method used is qualitative with a descriptive approach by analyzing secondary data from various reports, articles, and institutional publications. The findings indicate that productive zakat distribution—such as micro-business financing, skills training, and economic empowerment programs—has a significant impact on improving the welfare of zakat beneficiaries (mustahik). The implication of this research is the need to optimize zakat management in a sustainable, transparent, and economically empowering way, so that zakat becomes not only charitable but also transformative in socio-economic development.